Identifying gifted students in Puerto Rico: Validation of a Spanish translation of the Gifted Rating Scales. (May 2015) - Rosado, Javier I; Pfeiffer, Steven; Petscher, Yaacov
The challenge of correctly identifying gifted students is a critical issue. Gifted education in Puerto Rico is marked by insufficient support and a lack of appropriate identification methods. This study examined the reliability and validity of a Spanish translation of the Gifted Rating Scales-School Form (GRS) with a sample of 618 island-residing Puerto Rican students. Alpha values for the Spanish-translated version ranged from 0.98 to 0.99, comparable to those reported for the USA standardization sample. Scores on the Spanish-translated GRS correlated positively and significantly with classroom grades, Naglieri Non-verbal Test of Intelligence (NNAT) scores and with the island's local norm-referenced achievement test. Confirmatory factor analysis supported the six-factor model. Overall, findings provide evidence supporting the use of a Spanish-translated GRS for Puerto Rican island students.